2019
DOI: 10.1155/2019/4041801
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrumβ-Lactamases among Enterobacteriaceae Isolated from Urinary Tract Infections in Gaza Strip, Palestine

Abstract: Background Extended-spectrum β-lactamase-producing organisms causing urinary tract infections are increasing in incidence and pose a major impendence to health-care facility, having limited therapeutic options. This study aimed to assess the prevalence of ESBLs in Enterobacteriaceae isolates causing urinary tract infections in Gaza strip, Palestine, and to characterize β-lactamase types and associated resistance genes. Methods Eighty-five Enterobacteriaceae isolates were recovered from urinary tract infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 56 publications
5
20
0
Order By: Relevance
“…The molecular studies shown in Table 2 indicate that bla CTX-M was the most predominant ESBL trait among E. coli and ESKAPE pathogens, which evolved from 71.4% to 100%. A similar upward trend was also observed for bla TEM , bla OXA and bla SHV ESBL traits [ 82 , 83 ].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The molecular studies shown in Table 2 indicate that bla CTX-M was the most predominant ESBL trait among E. coli and ESKAPE pathogens, which evolved from 71.4% to 100%. A similar upward trend was also observed for bla TEM , bla OXA and bla SHV ESBL traits [ 82 , 83 ].…”
Section: Resultssupporting
confidence: 75%
“…The results shown in Table 1 indicate that in Palestine during 2000 to 2020, resistance to 3rd-generation cephalosporins, i.e., cefuroxime, cefotaxime, ceftazidime, was higher. Interestingly, lower resistance was reported against amoxicillin-clavulanic acid, aminoglycosides (gentamicin and amikacin), quinolones (ciprofloxacin), and imipenem [ 82 , 83 ]. Isolates expressing various ESBLs, characterized by double-disk potentiation method, showed relatively low ESBL rates 20 years ago (35.3%), which increased dramatically to 85.3% [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest antimicrobial resistance was for amikacin (19%); this percent is higher than the percent reported years ago, where the percent of amikacin resistance among GNB responsible for nosocomial bacteremia was 3.9%, while among community-acquired isolates, it was 1.8% [ 10 ]. On the other hand, it is lower than amikacin resistance among ESBL-producing isolates of Enterobacteriaceae in a study performed by Tayh et al in 2019 [ 11 ] which was 33.3%…”
Section: Discussionmentioning
confidence: 95%
“…Among ESBL genotypes, the Verigene ® system can detect CTX-M-1, CTX-M-2, CTX-M-8, CTX-M-9, and CTX-M-25, but not the remaining ESBL genotypes, SHV and TEM 11) . Based on a comprehensive review of several observational studies on ESBL-E genotype distribution in other countries [12][13][14] , CTX-M genotype groups are the predominant genotype group that constitute ESBL-E. However, there are no sufficient preceding reports regarding genotype distribution in clinical isolates from severe cases of adult UTI in Japan to anticipate the current genotype distribution precisely.…”
Section: Introductionmentioning
confidence: 99%